Nuchal translucency as a method of first trimester screening for aneuploidy in a South African population - Naidoo, Poovangela (My University, 2008)
ABSTRACT Nuchal Translucency as a method of First Trimester Screening for Aneuploidy in a South African population Background Chromosomal abnormalities constitute 15% of congenital abnormalities and 50% of pregnancy losses. Twenty-five percent of these will be Trisomy 21. Down’s syndrome has a birth incidence of 2 per 1000 and constitutes 25% of severe mental handicap in the developed world. Whereas the risk assessment focuses on Trisomy 21, the fetuses that screen positive are also known to contain other defects, which include anomalies such as cardiac defects, diaphragmatic hernias, neuromuscular disorders, and rare genetic syndromes. Objective To determine the effectiveness of nuchal translucency (NT) screening in predicting aneuploidy and structural abnormalities in a South African population Setting Chris Hani Baragwanath Hospital Fetal Medicine Unit Study design Descriptive Study Methodology The Fetal Medicine Unit database was reviewed and the records of patients who had undergone NT screening between July 2003 and July 2005 were retrieved. There were no exclusions. An adjusted risk was derived from the combination of age-related risk and the risk derived from nuchal translucency screening. A positive screen was denoted by an adjusted risk of more than 1/300 and a negative screen was denoted by an adjusted risk of less than 1/300. Results A total of 428 patients had first trimester screening during this period. Thirteen patients (3%) were lost to follow up. Of the 415 cases that were analyzed, 57 patients screened positive and 356 patients screened negative. In addition, 2 fetuses with acrania were detected. The mean age for both groups of patients was 30.1 years. The crown-rump length of fetuses with a positive screen was statistically significantly shorter than fetuses that screened negative. Of the 57 patients that screened positive 24 elected to have chorionic villus sampling (CVS) which resulted in the detection of 6 chromosomal abnormalities and 2 structural abnormalities. Of the remaining 356 patients, who had screened negative, 2 had an increased adjusted risk, and one chromosomal abnormality was detected in this group. Of the remaining 354 patients, 8 elected to have CVS because of a previous history of chromosomal abnormality. All of them proved to be normal. Conclusions The use of such screening has enabled prenatal karyotyping to be focused on pregnancies at highest risk for chromosomal abnormalities regardless of age.
Keywords: nuchal translucency screening; aneuploidy screening